2018
DOI: 10.1093/mnras/sty2022
|View full text |Cite
|
Sign up to set email alerts
|

A potential progenitor for the Type Ic supernova 2017ein

Abstract: We report the first detection of a credible progenitor system for a Type Ic supernova (SN Ic), SN 2017ein. We present spectra and photometry of the SN, finding it to be similar to carbon-rich, low-luminosity SNe Ic. Using a post-explosion Keck adaptive optics image, we precisely determine the position of SN 2017ein in pre-explosion HST images, finding a single source coincident with the SN position. This source is marginally extended, and is consistent with being a stellar cluster. However, under the assumptio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 86 publications
(135 reference statements)
6
62
0
Order By: Relevance
“…Thus despite their high luminosities they may be challenging to observe, requiring ultraviolet, or very blue-sensitive optical, detectors. Supernova 2017ein, the only SN Ic to have a progenitor system identified so far, occurred at a redshift ∼0.0027, with the candidate identified in archival Hubble Space Telescope (HST) imaging (Van Dyk et al 2018;Kilpatrick et al 2018). The star, if single, had an absolute F555W magnitude of −7.5.…”
Section: Future Possibilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus despite their high luminosities they may be challenging to observe, requiring ultraviolet, or very blue-sensitive optical, detectors. Supernova 2017ein, the only SN Ic to have a progenitor system identified so far, occurred at a redshift ∼0.0027, with the candidate identified in archival Hubble Space Telescope (HST) imaging (Van Dyk et al 2018;Kilpatrick et al 2018). The star, if single, had an absolute F555W magnitude of −7.5.…”
Section: Future Possibilitiesmentioning
confidence: 99%
“…Observed progenitors (in black) include the vanishing star N6946-BH1 (marked by a cross, Adams et al 2017), for which we have adjusted the luminosity to reflect an updated distance estimate (Eldridge & Xiao 2019), SN 1987A (marked by a star in the IIP section, Walborn et al 1987), several IIP SNe from Smartt (2015), type IIb and IIL SNe (both classified as II-other, and marked by dots and crosses respectively, Smartt 2015), SN 1993J (also a IIb event, Aldering et al 1994), the Ib progenitor of SN iPTF13bvn (Eldridge & Maund 2016) and finally the candidate Ic progenitor of SN 2017ein (Van Dyk et al 2018). The marked luminosity for 2017ein is an upper estimate, assuming that it was a single star (Kilpatrick et al 2018). This progenitor system is also indicated on the 'vanishing' panel (in purple) for reference.…”
Section: Classification Of Core-collapse Progenitor Modelsmentioning
confidence: 99%
“…This suggestion was supported by the discovery of the disappearing ∼ 25M red supergiant in NGC 6946 that likely underwent a failed SN (Gerke et al 2015;Adams et al 2017). However, recent studies by Maund (2017Maund ( , 2018 of the resolved stellar populations around Type IIP and strippedenvelope SNe, as well as the discovery of a possible progenitor system for Type Ic SN 2017ein (Kilpatrick et al 2018), suggest that even progenitors 18M can produce observable explosions. However, due to a number of factors discussed in Smartt (2015), the discovery rate of progenitor stars associated with SNe is small.…”
Section: The Initial Mass Functionmentioning
confidence: 99%
“…This result was later disputed by Bersten et al (2014a). More recently, Van Dyk et al (2018), Kilpatrick et al (2018) and Xiang et al (2019) identified a source in archival Hubble Space Telescope (HST) images covering the location of the type Ic SN 2017ein, with properties compatible with a WR star of M ZAMS ∼55 M (although the presence of a companion star could not be ruled out).…”
Section: Introductionmentioning
confidence: 99%